Base dependent pyrrolidine ring pucker in aep-PNA monomers NMR and PSEUROT analysis - Sharma, Nagendra K.; Ganesh, Krishna N. (Tetrahedron, 2010)
The aep-PNA is a chiral and cyclic PNA analogue which has a stronger and base dependent binding affinity with complementary DNA To understand the base dependent properties at monomer level the structural studies of aep-PNA-(T/C/A) monomers have been carried out focussing on the conformational analysis of pyrrolidine ring pucker in aep-PNA by H-1 NMR and the coupling constant data fitted into PSEUROT software The results indicate that the type of pyrrolidine pucker depends on the electronic nature of substituent implying the effect of pyrimidine or purine substituents in determining the ring pucker in monomers This may consequently influence the aep-PNA oligomer conformation Since pyrrolidine nucleic acids have emerged as an important class of PNA analogues present results may have importance for their future development (C) 2010 Elsevier Ltd All rights reserved
Keywords: A T G and C; aep PNA; Conformational analysis; DNA RNA and PNA; Pyrrolidine ring